THE DEVELOPMENT OF AUDIO VISUAL LEARNING MEDIA YOUTUBE VIDEO OF HINDU-BUDDHIST SITES IN BANYUWANGI TOWARDS HISTORY LEARNING IN GRADE X OF HIGH SCHOOL - Elya Sintya; Mohamad Na'im; Rully Putri Nirmala Puji (JURNAL HISTORICA, 2019)
History learning requires learning media to facilitate understanding of events and historical heritage. Youtube video audio visual learning media is a medium that is able to present images and videos to assits students understanding historical material. Banyuwangi Hindu-Buddhist sites were selected as material in development. The purpose of this study is to generate learning media which is adequated and validated, and to produce effective learning media to be enganged in historical learning. This study utilized Borg and Gall model which comprises of seven development stages, namely: (1) Research and information collection, (2) Planning, (3) Develop preminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main Field Testing, and (7) Operational Product Revision. The obtained product has been validated by content material expert, media and design expert. The content validation value obtained 93,3% means as "very good" and for media validation value is 91,66 % which categorize as "very good". The results of educators usage test show that 90% are categorized as "very good". Small group test results and large group test results obtained 0.6% with the effectiveness category "moderate", while 0.8% with the effectiveness category "high". Based on the explanation above, it can be concluded that audio visual youtube video learning media is effective to be enganged used in history learning process of grade X. Keywords: Learning Media Audio Visual Youtube Video, Banyuwangi Hindu-Buddhist Sites